2005
DOI: 10.1089/aid.2005.21.1011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HCV-RNA in Saliva of HIV-HCV Coinfected Patients

Abstract: The presence of HCV-RNA in saliva of patients with chronic hepatitis C provides a biological basis for the potential transmission of this virus. HCV viremia is particularly high in HCV-HIV-coinfected patients, which could favor the presence of HCV in their saliva. This study was designed to evaluate the prevalence of HCV in saliva of HCV-HIV-coinfected patients. Stimulated whole saliva was collected from 75 HCV-HIV-coinfected patients and 75 HCV controls. The presence of HCV-RNA in saliva was tested by a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Some studies reported prevalence values of 31–100% in saliva samples [5,7] and 38–85% in oral and gingival groove fluid samples [5,8]. Another study reported 52% of salivary HCV in a group of patients coinfected with HIV [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported prevalence values of 31–100% in saliva samples [5,7] and 38–85% in oral and gingival groove fluid samples [5,8]. Another study reported 52% of salivary HCV in a group of patients coinfected with HIV [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HCV could enter the saliva via peripheral blood mononuclear cells (PBMCs) (Roy et al 1998, Fabris et al 1999, Maticic et al 2001; however, the presence of HCV RNA in PBMCs and saliva have not been closely correlated (Young et al 1993). The detection of HCV RNA in saliva and the existence of a correlation between the viral load in saliva and other compartments have been demonstrated in previous studies (Mariette et al 1995, Hermida et al 2002, Eirea et al 2005 In this work, a quantitative PCR assay was used to determine HCV viral load levels in the saliva and serum of patients. The median viral RNA levels were 3.32 log 10 copies (2.1 x 10 3 copies/mL) in the saliva and 5.78 log 10 copies (1.21 x 10 6 copies/mL) in the serum (p < 0.0001) (A in Figure).…”
mentioning
confidence: 74%
“…Abe and Inchauspe (1991) demonstrated the transmission of HCV through human saliva, but the number of viral copies was not determined. Epidemiological studies suggest that the infective capacity of HCV RNA virions in saliva is low (De Cock et al 2004, Eirea et al 2005. Further studies are required to investigate the infective potential of HCVpositive saliva.…”
mentioning
confidence: 99%
“…Studies on the presence of HCV-RNA in saliva show an enormous variation of detection rates ranging from 0% to 100% (median, 42.5%) as reviewed recently (Ferreiro et al, 2005). However, in addition to the inferior quality of the molecular assays employed in those studies, results may be biased by several factors including HCV genotype, response to anti-HCV therapy, concomitant infections, and oral health status making comparisons difficult Eirea et al, 2005;Lins et al, 2005;Pastore et al, 2006]. Oral fluid was collected mainly by using non-standardized sampling methods and absorption phase-based saliva collection devices that may be responsible in addition for a decreased recovery of viral nucleic acids; however, this needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Testing oral fluid for the presence of viral nucleic acids including herpes simplex virus (HSV), varicella zoster virus (VZV), and hepatitis C virus (HCV) has been reported recently [Furuta et al, 2001[Furuta et al, , 2005Rey et al, 2001;Hermida et al, 2002;Dios et al, 2005;Eirea et al, 2005;Goncalves et al, 2005;Kaufman et al, 2005;Lins et al, 2005;Miller et al, 2005;Lock et al, 2006;Pastore et al, 2006]. In the vast majority of those studies, non-standardized sampling methods were carried out including spitting saliva in various collection containers or by using absorption phase-based saliva collection devices.…”
Section: Introductionmentioning
confidence: 99%